Implementasi Pendidikan Karakter Berbasis Islam Dalam Meningkatkan Akhlak Mulia Siswa - Ovi Mardatillah; Qonita Wardah; Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
This research aims to examine the implementation of Islamic-based character education in improving students' noble morals. The method used is [research method, for example: literature study, survey, or experiment]. The research results show that [brief research results, for example: there is a positive influence between Islamic-based character education and increasing students' noble morals]. The implication of this research is the importance of integrating Islamic values in the learning process to shape students' better character